Assistance for Business Feasibility of Village-Owned Enterprises (BUMDes) Respen Sakti Kulim Jaya Village Kempas District Indragiri Hilir - Yuslizar Yuslizar; Gunawan Syahrantau (KARYA ABDI, 2020)
Village-Owned Enterprises (BUMDes) is a company managed by the village community and its management is separate from the village government. Establishment of BUMDes aims to explore and optimize the potential of village entrepreneurs. As a business entity whose entire or most of its capital is owned by the village through direct participation from the village wealth which is separated to manage assets, services, and other businesses for the maximum welfare of the village community. Whereas BUMDes Respen Sakti which was established by the newly established Kulim Jaya village government has not been able to run a business properly and needed business feasibility assistance. Therefore, the agriculture faculty of the Agribusiness Study Program of the Islamic University of Indragiri conducts business feasibility assistance for BUMDes in the Kulim jaya Village, Kempas District . The method of carrying out community service activities is carried out with data collection techniques through lectures. Source of data obtained are secondary data with qualitative data analysis. Business feasibility assistance conducted by the Faculty of Agriculture Agribusiness Study Program of Indragiri Islamic University to the Village-Owned Enterprises (BUMDes) of the Respen Sakti Kulim Jaya Village is going well. This can be seen from the ability of BUMDEs in managing and running 2 (two) types of businesses, namely LPG 3 Kg GAS and Electronic Goods Credit. In addition, BUMDEs Respen Sakti is able to obtain increased revenue and sales of 3 Kg LPG GAS and BUMDes Respen Sakti is able to provide services to the demand for electronic goods needed by the community